Locked [videorecording (DVD)] - Ross, Michael Arlen; Skarsgård, Bill; Hopkins, Anthony; Cartwright, Ashley; Eklund, Michael; 4x4 (Motion picture) (Paramount, 2025)
When Eddie breaks into a luxury SUV, he steps into a deadly trap set by William, a self-proclaimed vigilante delivering his own brand of twisted justice. With no means of escape, Eddie must fight to survive in a ride where escape is an illusion, survival is a nightmare, and justice shifts into high gear.